Keabsahaan Pengangkatan Kepala Pemerintahan Negeri Lisabata Timur Kabupaten Maluku Tengah - Tomalima, Ilham Agus; Nendissa, Renny Heronia; Lainsamputty, Natanel (Faculty of Law, Universitas Pattimura, 2023)
The village government system in Maluku in the customary regime is known as State government and generally applies to Ambon Island and Central Maluku Regency. State government is the basis of indigenous peoples and has clear land and sea territorial boundaries called petuanan country, and a government system that is genealogical or based on lineage. The term Negeri does not come from the native language of this area or